Evaluation of an electronic, patient‐focused management system aimed at preventing cytomegalovirus disease following solid organ transplantation. Issue 2 (10th February 2020) - Ekenberg, Christina; da Cunha‐Bang, Caspar; Lodding, Isabelle P.; Sørensen, Søren S.; Sengeløv, Henrik; Perch, Michael; Rasmussen, Allan; Gustafsson, Finn; Wareham, Neval E.; Kirkby, Nikolai; Kjær, Jesper; Helleberg, Marie; et al.
Abstract: Background: Cytomegalovirus (CMV) infection is common among solid organ transplant (SOT) recipients and may cause CMV disease. To optimize the implementation of existing prevention strategies, the Management of Post‐transplant Infections in Collaborating Hospitals (MATCH) program was developed. Two key performances of MATCH (diagnosing CMV infection at low viral load (VL) and before the onset of CMV disease) were assessed prior to, during and after the implementation of MATCH. Methods: The MATCH program included a personalized surveillance plan, prophylaxis and preemptive therapy determined by the recipient's risk of CMV infection. The plan was composed through predefined algorithms and implemented through harvesting of real‐time data from medical records. Risk of CMV disease was compared for recipients transplanted during and after vs prior to the implementation of MATCH. Lung and non‐lung transplants were analyzed separately. Results: A total of 593, 349, 520, and 360 SOT recipients were transplanted before (2007‐2010), during (2011‐2012), early after (2013‐2015), and late after (2016‐2017) implementation of MATCH with an observed reduction of diagnostic VL ( P  < .001) over time. Risk of CMV disease was reduced among non‐lung transplant recipients transplanted during (adjusted hazard ratios [95% CI] 0.15 [0.04‐0.54], P  = .003), early after (aHR 0.27 [0.11‐0.63], P  = .003), and late after (aHR 0.17 [0.06‐0.52], P  = .002) compared with prior to MATCH. No significant change was observed among lung transplants. Conclusion: Implementation of CMV preventive strategies through MATCH was associated with a reduced risk of CMV disease among non‐lung transplant recipients. Furthermore, the limitations of VL as a sole indicator for CMV disease in lung transplants were emphasized.